A new attempt for the detection of potential water-bearing structures in tunnels via hydraulic tomography: The first numerical investigation. (May 2023) - Wang, Xintong; Xu, Zhenhao; Hu, Jie
Graphical abstract: Highlights: HT was implemented to detect potential water-bearing structures in tunnels. Embedded water-bearing structures are identified in two synthetic numerical models. Comparison was given between the steady-state and transient hydraulic tomography. The reliable hydraulic properties were inverted by adding geological information. Abstract: Water-bearing geological structures in front of the tunnel and underground engineering are prone to water inrush hazards, which seriously threaten construction safety. This study investigated the potential of hydraulic tomography (HT) in detecting water-bearing structures to prevent groundwater hazards in tunnels. We established two synthetic heterogeneous aquifers with two different water-bearing structures, fractures and cavern zones. A comprehensive HT inversion analysis was performed using hydraulic head records generated by forward hydraulic tests. The results show that 1) sufficient pumping and observation wells can assist in capturing water-bearing structures and hydraulic properties; 2) transient hydraulic tomography (THT) inversion has a better effect than steady-state hydraulic tomography (SSHT) inversion since the temporal variation of head records carries non-redundant characteristics and distribution information of water-bearing structures; 3) inverted hydraulic conductivity and specific storage fields are positively correlated with observed heads at the end and early stages of the pumping test, respectively; 4) taking geological information as a prior can greatly assist in mapping potential water-bearing structures. This study can provide valuable guidance for detecting water-bearing structures in tunnel and underground engineering and formulating effective control schemes for water inrush hazards.